Disability in post Covid-19 Era - Ellyana Sungkar (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
Disability is an impaired condition in physical, mental, cognitive, or developmental aspect that interfereswith, or limits a person’s ability to engage in certain tasks or actions or participate in activities dailyliving and interactions. Based on International Classification Functional Perception, an interactionbetween individuals with a health condition, such as cerebral palsy, spina bifida, neuromusculardisease etc with personal and environmental factors will result in a disability condition including,limited social support and education, inaccessible transportati on as well.